Rice Wholesale and Retailing Business in Atok, Benguet, Philippines: An Assessment of Viability - Guansi, Dr. Steve S. (IJRDO - Journal of Business Management, 2018)
The viability and profitability of the proposed rice wholesale and retailing business in Atok, Benguet, Philippines can assume vital play in the sustainability of its target consumers. Operating as a small and medium enterprise, it can sufficiently satisfy the demand of people living within the vicinity of the target area. With the projected population and income listed from year 1 to year 5 of the proposed operation, it shows that population and income of people of Atok, Benguet increase every year. The yearly increase shows high demand of rice. Also based on supply analysis, expected competitors who are existing retailers in the area cannot completely satisfy the demand of people because they only cater to about less than fifty percent of the total consumption requirement per year (basis of consumption is in cavans) which means, response to demand is too high. It is noted however that the unsatisfied demand by the existing retailers will be satisfied by the prospect rice retailing business. In the management aspect, the proposed business follows the structure of a single proprietorship and implements direct flow of authority and concentrated responsibility. The management conducts job analysis program to evaluate and check employment qualification, training and development. Renumeration of selected workers is expected to be given in accordance to the law as prescribed in the Labor Code of the Philippines. Personnel policies are to be monitored and strictly implemented. This means that management is maintaining conduct and good governance to meet its stated vision, mission, objectives and values. Five hundred thousand pesos (P500,000.00) start – up capital can adequately finance all other resources necessary for operation. For the first five years of operation, the proprietor rents a building conducive to consumers. This is to ensure nearness to market. Provided that business meets profitability evidence by its Return on Investment status (ROI) in the succeeding years, construction of a single – storey building follows. The location of business in however characterized by its accessibility and proximity to market because the site is within the central business district of Atok Municipality. Prior to legal operation, socio – economic desirability is also expected to be promoted. Social responsibility of the business is given the priority equivalent to service and development. This social obligation is expected to promoted public welfare in some varied ways. The local government of Atok, Benguet can increase its revenues from business taxes. The proposed business can contribute local employment, customers’ access to affordable rice products, quality rice grains and immediate services. Along with the planning and decisions toward effective finance and marketing management, the proposed business is highly recommended for investment.